Tools and AI in stylistic analysis - Fahmi Alhubilah; Asep Sopian (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
This research constitutes a systematic literature review that investigates the application of tools and Artificial Intelligence (AI) in stylistic analysis. The objective of the evaluation is to identify the various types of tools and AI utilized in stylistics and to assess their respective advantages and disadvantages in facilitating language analysis. Since the selection of data sources is critical, the relevance of each article was carefully assessed to ensure analytical accuracy and applicability of the findings. Utilizing the Systematic Literature Review (SLR) methodology, nine pertinent articles published between 2015 and 2025 were examined according to specific inclusion criteria. The study’s findings reveal that tools such as Voyant Tools, WordSmith, LIWC, and StyloMetrix are extensively employed to analyze linguistic and stylometric characteristics across different text types, including poetry, emails, and texts generated by AI. While AI has demonstrated its ability to improve efficiency, objectivity, and analytical depth, it continues encountering difficulties in capturing linguistic subtleties and cultural contexts. This study advocates for a collaborative approach between humans and AI to achieve more thorough and precise stylistic analyses in education, literature, and forensic linguistics.